Factors shaping student satisfaction in e learning environment - Mat Ali, Syukrina Alini; Mohamad Yunus, Noor’ain; Abdul Kadir Jailani, Sri Fatiany; Mansor, Aida Azlina; Mohamd Shobri, Nor Diyana (Universiti Teknologi Mara Selangor, 2024)
The aim of this study is to explore the relationship between online platforms, instructor support, and teaching quality and the level of satisfaction among students. This study utilized an online survey targeting students from the Faculty of Business and Management at Universiti Teknologi MARA, Selangor. In targeting this population, the researcher used a convenience sampling technique and collected 160 samples. Quantitative data was analyzed using a statistical analysis tool called SPSS to reveal statistically significant between these variables. Current research evidence points towards instructor support as having a positive correlation with attitudinal behavioural outcomes for students, particularly in regard to feedback and correspondence about online courses. Moreover, having high-quality teachers impacts learners’ overall satisfaction with the subject they are learning, quality content, and technique. The readiness to participate in virtual classrooms also depends on the usability of the platforms used, as convenient interfaces increase satisfaction. This research underlines the need for well-ordered procedures of instructors and students’ communication to provide supportive educational environment of online classrooms. There are recommendations that institutions should consider supporting instructors to provide better learning experiences on the platform and redesign the platform to increase its effectiveness. Subsequent research should include diverse student demographics by identifying how different factors affect satisfaction in environments for online learning.